Pathogenic effects of nematode parasite Eustrongylides sp. larvae on serum LH level and histology of gonads of freshwater fish, Clarias gariepinus - Ahmad Mir, Tahir; Kaur, Pinky; Manohar, Susan (Recent Research in Science and Technology, 2012)
Â Present study was conducted to known the pathological effects caused by nematode parasite, Eustrongylides sp. larvae on serum LH level and histology of gonads of freshwater fish, Clarias gariepinus. The nematode parasite Eustrongylides occurs in the body cavity of its host Clarias gariepinus and inhibits gonadal development. A significant decrease in the gonadotropin hormone (LH) in the blood stream was recorded. LH reduction was recorded to be the 50% less as compared to the normal fishes. Histopathological studies of testes revealed disorganized testicular structure, germinal epithilium was disrupted and reduction in spermatozoa was reported. Histology of infected ovaries showed the appearance of interfollicular spaces, degeneration of follicular wall tissues and their egg envelops ruptured observed.